A simple way to prepare nanosize NiO powder by mixing acidic Ni compound with basic Ni compound - Cheong, D.-S.; Yun, D.H.; Park, S.H.; Kim, C.-S. (2009)
Nanosize NiO powder was prepared by mixing acidic nickel nitrate with basic nickel carbonate. The particle size and morphology of NiO were mainly governed by the mole ratio of the nitrate to the carbonate. The effects were studied by DSC, XRD, FTIR, and SEM. Heat treatment conditions influence the particle size distribution of produced NiO powder extensively for the case of 3N7C (3 moles of the nitrate and 7 moles of the carbonate) and 4N6C, but only slightly for 1N9C and 2N8C. Uniform pseudospherical NiO particles were obtained in 50∼70 nm for 1N9C and 30∼60 nm for 2N8C by calcination at 750°C for 2 h.
Keywords: Calcination effects; DSC; Nano-size; Nickel carbonate; Nickel nitrate; Calcination; Carbonation; Nitrates; Particle size analysis; Nickel